2003
DOI: 10.1258/095148403762539112
|View full text |Cite
|
Sign up to set email alerts
|

Hospital efficiency and patient satisfaction

Abstract: The objective of this study was to investigate the relationship between efficiency and patient satisfaction for a sample of general, acute care hospitals in Ontario, Canada. A measure of patient satisfaction at the hospital level was constructed using data from a province-wide survey of patients in mid-1999. A measure of efficiency was constructed using data from a cost model used by the Ontario Ministry of Health, the primary funder of hospitals in Ontario. In accordance with previous studies, the model also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 7 publications
10
27
2
Order By: Relevance
“…29 Hospital complexity increases with size, and patients may feel more alienated in big hospitals, resulting in less-positive experiences. 15,30 Lower expectations among patients in small hospitals is a possible explanation for their better scores. 15 Likewise, patients admitted to hospitals that have a university affiliation may expect a high quality of the services and therefore might more easily become disappointed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Hospital complexity increases with size, and patients may feel more alienated in big hospitals, resulting in less-positive experiences. 15,30 Lower expectations among patients in small hospitals is a possible explanation for their better scores. 15 Likewise, patients admitted to hospitals that have a university affiliation may expect a high quality of the services and therefore might more easily become disappointed.…”
Section: Discussionmentioning
confidence: 99%
“…15,30 Lower expectations among patients in small hospitals is a possible explanation for their better scores. 15 Likewise, patients admitted to hospitals that have a university affiliation may expect a high quality of the services and therefore might more easily become disappointed. Also, many patients are familiar with their district hospital and possess knowledge about mitigating circumstances to modify their judgment if they experience low quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that chronically ill and healthy respondents experienced the same satisfaction with community care services. Several studies [29-31] discussed the questionnaire’s design, validity and reliability as it related to patient satisfaction which found that nursing and doctor categories were most notable, and several studies approached different aspects of patient satisfaction [32,33]. …”
Section: Introductionmentioning
confidence: 99%
“…Cost containment is clearly a major issue for administrators, but unfortunately, resource 66 HEALTH MARKETING QUARTERLY cutbacks may ultimately lead to increased patient dissatisfaction (Pink, Murray, and McKillop, 2003). As Schumacher (2005) asserts, "it seems that every year, physicians, nurses, and other members of the delivery team are expected to do more with less" (p. 28).…”
Section: Job Resourcefulness and The Hospital Settingmentioning
confidence: 99%